Sickle Cell Disease and Antimicrobial Resistance: A Systematic Review and Meta-Analysis - Bismark Opoku-Asare; Onyansaniba K. Ntim; Aaron Awere-Duodu; Eric S. Donkor (Infectious Disease Reports)
Background/Objectives: Antimicrobial resistance (AMR) is increasingly rising due to antimicrobial overuse and misuse. In sickle cell disease (SCD) care, frequent antibiotic use drives the rapid emergence of AMR, threatening treatment options and patient lives. This systematic review synthesizes data on AMR with regard to SCD patients for the first time. Methods: A comprehensive database search for articles published in English was conducted in PubMed, Scopus, ScienceDirect, and Web of Science, with no restriction set for the year of publication. The DerSimonian–Laird method was applied to derive the pooled prevalence, while the Mantel–Haenszel method was used to calculate the pooled odds ratio. Results: A total of 18 eligible studies covering 3220 SCD patients published between 1996 and 2024 were included in this review. The common bacterial pathogens reported in the included studies were Streptococcus pneumoniae (10 studies), Staphylococcus aureus (10 studies), and Escherichia coli (4 studies). For S. aureus, the pooled resistance was highest for penicillins (ampicillin = 100%; penicillin = 93.64%; and amoxicillin = 77.82%) followed by cefuroxime (51.23%). The pooled prevalence of methicillin-resistant S. aureus (MRSA) was 19.30%. SCD patients had 2.89 and 2.47 times higher odds of being colonized or infected with penicillin-resistant and erythromycin-resistant S. aureus strains, respectively. For S. pneumoniae, resistance prevalence was highest for co-trimoxazole (81.1%), followed by penicillin (47.08%). The pooled prevalence of multidrug-resistant (MDR) S. pneumoniae isolates was 32.12%. The majority of the studies included (n = 14, 77.8%) were of moderate quality according to the modified STROBE checklist. Conclusions: This review reveals a high prevalence of AMR with regard to SCD patients. SCD patients have an increased risk of resistance to penicillin and co-trimoxazole across several bacterial pathogens. The limited geographical distribution of the included studies underscores the urgent need for expanded AMR research on the subject, especially in regions with high SCD burden.